Social responsibility and environmental sustainability. The case study of Vale (Brazil) - Figueredo, I. (2017)
Corporate social responsibility deals with companies' actions aiming a positive impact namely on environment, consumers, employees or communities, for example. It requires a set of duties and obligations, in relation to the society and to the communities in which the organization is operating. In Brazil, the corporate social responsibility is still a big challenge, since the actions of social responsibility have not contributed effectively to improve the living conditions of society and the transformation of existing social reality. This study emphasizes the perspective of environmental sustainability that underpins the more general concept of social responsibility. Besides, it is presented the case study of the company Vale, carrying out business in Brazil.